2018
DOI: 10.1155/2018/8579026
|View full text |Cite
|
Sign up to set email alerts
|

A Vaginal Angiomyofibroblastoma as a Rare Cause of a Prolapsing Vaginal Mass: A Case Report and Review of the Literature

Abstract: Introduction Angiomyofibroblastoma (AMFB) is a rare, benign, mesenchymal cell tumour which presents as a slow-growing mass. It is most commonly seen in the vulva and is often mistaken for Bartholin's abscess. It is histologically diagnosed by the presence of stromal cells intermingled with small blood vessels. It is morphologically similar to cellular angiofibroma and aggressive angiomyxoma, the latter of which is locally invasive and has a possibility of metastasis and a high risk of local recurrence. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Vaginal prolapse has been documented in cattle, goats, sheep, camels, dogs, cats, and women. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To authors' knowledge, it has not been reported in mares. A mare had cervical hyperplasia and mass that led to vaginal protrusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaginal prolapse has been documented in cattle, goats, sheep, camels, dogs, cats, and women. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To authors' knowledge, it has not been reported in mares. A mare had cervical hyperplasia and mass that led to vaginal protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Other factors include, excess perivaginal fat, prior perivaginal tissue injury, poor conformation, and incompetence of the constrictor vestibule or vulvae musculature. 4,6,8,9 Vaginal prolapse most commonly occurs in multiparous women among the ages of 40 -70. [7][8][9] In most species, it occurs during the last few weeks of pregnancy when intraabdominal pressure is maximum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An AMFB is often encountered in the vicinity of the Bartholin gland. Both conditions produce a mobile, generally painless mass that may interfere with walking, sitting and intercourse [12]. Both masses are well circumscribed [13].…”
Section: Discussionmentioning
confidence: 99%
“…Angiomyofibroblastoma is morphyologically familiar to aggressive angiomyxoma as they share many features such as painless and slow-growing mass. But histopathologically it displays superficial vascular mucinous, clear boundary, more smooth muscle components in stromal matrix and presents more pathological thin-walled blood vessels [5]. It's usually negative for desmin, smooth muscle actin, vimentin and CD34 as the same time.…”
Section: Case Presentationmentioning
confidence: 98%